2018
DOI: 10.1002/hyp.11429
|View full text |Cite
|
Sign up to set email alerts
|

Multiple model combination methods for annual maximum water level prediction during river ice breakup

Abstract: The Athabasca River is the largest unregulated river in Alberta, Canada, with ice jams frequently occurring in the vicinity of Fort McMurray. Modelling tools are desired to forecast ice‐related flood events. Multiple model combination methods can often obtain better predictive performances than any member models due to possible variance reduction of forecast errors or correction of biases. However, few applications of this method to river ice forecasting are reported. Thus, a framework of multiple model combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 64 publications
(80 reference statements)
0
19
0
1
Order By: Relevance
“…In the Athabasca River along the Fort Mc-Murray, the flood water level is 246.8 m a.s.l. Above this level, the low-lying areas along the left bank of the Clearwater River gets flooded (Sun and Trevor, 2018). Thus, the estimation of PMFice to be approximately 250.43 m a.s.l.…”
Section: Calculating the Probable Maximum Ice-jam Stagingmentioning
confidence: 99%
“…In the Athabasca River along the Fort Mc-Murray, the flood water level is 246.8 m a.s.l. Above this level, the low-lying areas along the left bank of the Clearwater River gets flooded (Sun and Trevor, 2018). Thus, the estimation of PMFice to be approximately 250.43 m a.s.l.…”
Section: Calculating the Probable Maximum Ice-jam Stagingmentioning
confidence: 99%
“…As one of popular ensemble learning methods, stacking involves a higher-level (metalevel) learner (combining model) to combine lower-level (base-level) learners (base model) to achieve greater predictive performance (Wolpert, 1992;Ting and Witten, 1999). In this sense, stacking is similar to the multiple model combination method (Sun and Trevor, 2018a). Although stacking is usually employed to combine different-type base learners built by multiple learning algorithms, it can be used to combine same-type base learners with different structures or calibrated parameters as well.…”
Section: Sca Ensemblementioning
confidence: 99%
“…However, few applications of SCA to river ice forecasting are reported. Meanwhile, it has been reported that stacking ensemble learning can improve the overall performance through effective combinations of different base models (Erdal and Karakurt, 2013;Sun and Trevor, 2017;Sun and Trevor, 2018a). Thus, further improving the accuracy of SCA predictability using the stacking ensemble learning paradigm and its application to river ice forecasting are desired.…”
Section: Introductionmentioning
confidence: 99%
“…According to Maier and Dandy (), measures that have been applied to maximize the use of available data sets include the use of a “hold‐out method,” which involves withholding a little portion of the data for validation and training the network on the remaining data sets. Once a significant degree of convergence is observed in the network using the validation set, a different subset of data is withheld and the process is repeated until the network attains significant generalization for the entire data set (Sun & Trevor, ). Another method that is being used to maximize available data is the “cross‐validation” technique.…”
Section: Model Development Processesmentioning
confidence: 99%